"John owen : reformed catholic, renaissance man" - "Trueman, Carl R" (Hampshire, 2007)
John Owen is considered one of the sharpest theological minds of the seventeenth century and a significant theologian in his own right, particularly in terms of his contributions to pneumatology, christology, and ecclesiology. Carl Trueman presents a major study of the key elements of John Owen's writings and his theology. Presenting his theology in its historical context, Trueman explores the significance of Owen's work in ongoing debates on seventeenth century theology, and examines the contexts within which Owen's theology was formulated and the shape of his mind in relation to the intellectual culture of his day - particularly in contemporary philosophy, literature and theology. Examining Owen's theology from pneumatological, political and eschatological perspectives, Trueman highlights the trinitarian structure of his theology and how his theological work informed his understanding of practical Christianity. With the current resurgence of interest in seventeenth century Reformed theology amongst intellectual historians, and the burgeoning research in systematic theology, this book presents an invaluable study of a leading mind in the Reformation and the historical underpinnings for new systematic theology.
Keywords: "Owen, John-doctrine"